Quantitative cervical vertebral maturation assessment with the use of Cone-Beam computed tomography - Ríos León, Rocío del Pilar (2018)
Objective: To evaluate a quantitative method of bone maturation in cervical vertebrae in 14 Cone Beam computed tomographies of children aged 9 to 15 years old obtained from the archive of the Radiologic Service of the School of Dentistry at the National University of San Marcos. Methods: A retrospective, descriptive and transversal study was carried out. The sample was for convenience of 14 tomographies of children (seven male), these were clinically justified images, previously taken with the Picasso Master 3D - FOV 20x15 and processed with the EzImplant software; the head was positioned with reference to the Frankfort plane and the cuts were made. We used a quantitative method that established four stages of maturation in an objective way by means of an equation that used three measurements in the vertebrae C2, C3 and C4. Results: The highest percentage of children was found in the deceleration period. In the high-speed period, the highest values were found for the female sex with an average age of 11 years. Conclusions: The quantitative method described was simple, practical and applicable through Cone Beam computed tomography showing good results.